If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + -3g = 20 + 2g Solving 21 + -3g = 20 + 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 21 + -3g + -2g = 20 + 2g + -2g Combine like terms: -3g + -2g = -5g 21 + -5g = 20 + 2g + -2g Combine like terms: 2g + -2g = 0 21 + -5g = 20 + 0 21 + -5g = 20 Add '-21' to each side of the equation. 21 + -21 + -5g = 20 + -21 Combine like terms: 21 + -21 = 0 0 + -5g = 20 + -21 -5g = 20 + -21 Combine like terms: 20 + -21 = -1 -5g = -1 Divide each side by '-5'. g = 0.2 Simplifying g = 0.2
| 5a+4a-6b= | | (9-p)3= | | y=0.5x^3-2x+2.5 | | e^2+7e+10= | | 2c+19=65 | | p(-4)=-9+p | | 16(3x-.25)= | | 0.5x^3-2x+2.5=y | | (z+5)(z-8)=0 | | 0.5x^3-2x+2.5=0 | | -4=-(x-3)+6(x-2) | | 5(c-8-3)-3(2c+12)=-84 | | 2x+x+2=5x-10 | | .05x+.10(200-x)=.45x | | 0.09w=1.8 | | (a+4)(a+5)=0 | | -132=-39 | | -(c+10)+3(2c-6)= | | -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 | | 3(2z-1)=6z+5 | | -28=-7(1-8b)-5(4b-3) |